The Pressure Is On: How Geopolitical Tensions Impact Institutional Fiscal and External Stability Responses - António Afonso; José Alves; Sofia Monteiro (Center for Economic Studies and ifo Institute (CESifo), 2024)
In this article, we study the effects of geopolitical risks and world uncertainty on time-varying fiscal and external sustainability coefficients. We use Schlicht's (2021) methodology to estimate time-varying fiscal and external sustainability coefficients for the EU for 27 economies between 2001Q4 and 2022Q3. While fiscal sustainability coefficients derive from the government revenues and expenditures relationship, external sustainability coefficients were computed from the exports' responses to changes in imports. Our results show that geopolitical risks are always associated with lower fiscal and external sustainability, although with a stronger effect when took into consideration the home geopolitical risk. Moreover, the effects of geopolitical tensions are much stronger on external accounts' sustainability than on fiscal sustainability. The magnitude of GPR detrimental effects on external sustainability can be 3 to 6 times higher, approximately, when compared to public finances' sustainability. Lastly, geopolitical tensions in border countries have a negative spillover effect on the sustainability of domestic external accounts.
Keywords: E62; F15; F42; H62; H87; 330; economic integration; geopolitical risks; fiscal sustainability; external sustainability; time-varying coefficients